Uji Sensitisasi Dermal Masker Gel Kombinasi Ekstrak Ampas Daun Teh dan Air Cucian Beras - Annisa, Andi Nurul; Utaminingrum, Wahyu; Genatrika, Erza (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2019)
The combination of tea leaf dregs extract and rice washing water as a peel-off gel mask was found to be stable up to 28 days of storage and had an IC50 value 20.4 ppm. This potential can provide an optimal effects as cosmetic ingredients.However, to meet the regulatory requirements of Badan Pengawas Obat Makanan (BPOM) RI and ISO 10993, a dermal sensitization test also need to be done. The aim of this study was to determine the dermal sensitization reaction from peel-off gel mask containing a combination of tea leaf dregsextract (Camellia sinensis L.) and rice washing water (Oryza sativa L.) in test animal. Thisstudy was designed based on experimental laboratory methods and sample selection by simple random sampling. The intervention was given based on posttest-only control group design. The test results for dermal sensitization were determined using the Guinea Pig Maximization Test (GPMT) method. The results showed erythema and edema reactions according to the Magnusson and Kligman scale after administration of peel-off gel masks as samples in the topical tests in test animals, appeared on the 11th day and in the challenge test appeared on the 24th day. This was due to incubation period for one week where the hypersensitivity state can develop, so that this reaction is also called the delayed hypersensitivity reaction